Thermal Conductivity of Thermally Insulated Concretes in a Nuclear Safety Vessel of Reactor Vault: Experimental Interpretation - M. Anish; T. Arunkumar; J. Jayaprabakar; Sami Al Obaid; Saleh Alfarraj; M. M. Raj; Assefa Belay (Advances in Materials Science and Engineering)
Thermally insulated concretes are a type of alternative building material that helps improve thermal efficiency in nuclear reactor vault safety vessel applications. The experimental results of thermal conductivity values of lightweight concrete materials at various temperatures are presented in this paper. To minimize heat conduction in concrete, different lightweight aggregates and vermiculite are employed as coarse aggregate alternatives.Both linear and plane heat source approaches are used to calculate the thermal conductivity values of the specimens. The findings emphasize that increasing the proportion of lightweight particles in concrete may dramatically lower the thermal conductivity, with the kind of lightweight aggregates having a vital role in thermal insulation. The inclusion of micron-sized vermiculite decreases heat conductivity even further; however, the effect is less obvious than that of lightweight particles.